Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning (PBL) Di Kelas IV SDN 18 Air Tawar Selatan Padang - Rahmadaniati, Shekar; Nasrul, Nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to describe the improvement of integrated thematic learning processes with a problem based learning approach in class IV SDN 18 Air Tawar Selatan, Padang City. This type of research is classroom action research using qualitative and quantitative approaches. The results of the observation of RPP in cycle 1 obtained an average of 89.76%, and cycle 2 gained an average of 97.72%. Aspects of students in the first cycle with a percentage of 88.38% increased in the second cycle to 96.42%. This proves the scientific approach can improve student learning processes.